MEMBANGUN KEMAMPUAN BERPIKIR LOGIS DENGAN MIND MAPPING: METODE KREATIF DALAM PENDIDIKAN: (Quasi Eksperimen pada Mahasiswa Pendidikan Ekonomi Universitas Kuningan) - Atin Nuryatin (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to enhance the logical thinking skills of students through the application of the mind mapping method in studying microeconomics, namely on the topic "Consumer Behavior." Utilizing a quasi-experimental research design with a one-group pretest-posttest model, the study was carried out on 18 students of the Economics Education Study Program of Kuningan University. Data was collected through tests of logical thinking and classroom observations and analyzed using the Wilcoxon test. Outcome of the analysis was that the average score increased from 62.17 in pre-test to 75.67 in post-test. There was an improvement in the median, mode, minimum, and maximum as well as the decrease of the standard deviation, which meant that student learning outcomes became symmetrical. The Wilcoxon test provided a p-value of 7.63 × 10⁻6 (< 0.05), which confirmed that there was a considerable difference between post-test and pre-test scores. A measure of effect size 0.88 shows an extremely significant effect of the Mind Mapping technique on the students' logical thinking capability. From observations in the classrooms, it was also revealed that students improved in identifying information, establishing cause-and-effect relationships, classifying data, developing evidence-based arguments, and drawing logical conclusions. Therefore, it can be argued that the use of the Mind Mapping learning technique significantly enhances students' critical thinking ability through the reinforcement of knowledge and concepts, thereby their performance in microeconomics, particularly in the topic of consumer behavior. Keywords: mind mapping, logical thinking skills, active learning, microeconomics.